2012
DOI: 10.1590/s0103-51502012000100007
|View full text |Cite
|
Sign up to set email alerts
|

Influência dos corticosteroides inalatórios nas pressões respiratórias máximas de crianças escolares asmáticas

Abstract: INTRODUÇÃO: O corticosteroide inalatório (CI) é o principal medicamento utilizado no tratamento profilático e de manutencão da asma. Graças à superdosagem ou ao uso prolongado dos CIs podem surgir efeitos colaterais como a redução do crescimento ósseo, supressão adrenal e miopatia. OBJETIVOS: Avaliar a influência dos corticosteroides inalatórios nas pressões inspiratórias (PImax) e expiratórias (PEmax) máximas de crianças escolares asmáticas. MATERIAIS E MÉTODOS: Estudo transversal, observacional, que incluiu … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…Respiratory muscles have been studied more often than peripheral muscles in asthma, but not in severe asthma. In addition, the available evidence on respiratory muscle strength in pediatric asthma is limited and contradictory, given that some studies found no differences between asthmatics and healthy subjects [11][12][13], and others found a decrease in only one inspiratory or expiratory strength [14,15].…”
Section: Marcolin Et Almentioning
confidence: 99%
“…Respiratory muscles have been studied more often than peripheral muscles in asthma, but not in severe asthma. In addition, the available evidence on respiratory muscle strength in pediatric asthma is limited and contradictory, given that some studies found no differences between asthmatics and healthy subjects [11][12][13], and others found a decrease in only one inspiratory or expiratory strength [14,15].…”
Section: Marcolin Et Almentioning
confidence: 99%